When governments create unfreedom: rehumanizing migrant domestic workers. (2nd October 2019) - Dumont-Robillard, Myriam
ABSTRACT: Taking the new Canadian legislation on migrant domestic workers as an illustration, this article suggests that framing temporary migrant work programs in a discourse of economic labor markets has a dehumanizing effect and tends to obscure both the reality experienced by the workers (within and beyond the workplace) and the forces at play in the creation of these experiences. Ultimately, such a discourse can even serve to justify regulatory frameworks that violates workers' basic human rights and maintain global inequalities. Building on the concepts of informality, unfree labor relations and precarious work, we suggest that a rehumanization process built around the workers dignity is necessary, in order to fully recognize the responsibility of governments in the construction of migrant domestic workers' unfreedom and thus bring to light the illegality of these types of regulatory frameworks. In the end, respecting temporary migrant workers' dignity should translate into an institutional change where these workers not only get to participate in the law-making processes, but also in the very framing and shaping mechanisms of these institutions.